Thermal-mechanical based Soft Tissue Deformation for Surgery Simulation - Zhong, Yongmin; Shirinzadeh, B.; Smith, J.; Gu, C. (BRILL ACADEMIC PUBLISHERS, 2010)
Soft tissue deformation is of great importance to virtual reality-based surgery simulation. This paper presents a new methodology for the modeling of soft tissue deformation. This methodology converts soft tissue deformation into thermal–mechanical interaction according to the continuum mixture theory of soft tissues, and thus heat conduction of mechanical load and non-rigid mechanics of motion are combined to govern the dynamics of soft tissue deformation. The mechanical load applied to a soft tissue to cause a deformation is distributed among mass points of the soft tissue according to the principle of heat conduction. A thermal–mechanical model and associated model construction algorithms are developed to describe the distribution of the mechanical load in the tissue. A heat flux-based method is established for derivation of internal forces from the distribution of the mechanical load. Real-time interactive deformation of virtual human organs with force feedback has been achieved by the proposed methodology for surgery simulation. The proposed methodology not only accommodates isotropic, anisotropic and inhomogeneous materials by simply modifying thermal conductivity constants, but it also accepts local and large-range deformation.